2020
DOI: 10.9734/afsj/2020/v17i230190
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Allamanda cathartica Seed Oil: A Novel Source of Plant Oil Substitute for Industrial Processing

Abstract: Oil from Allamanda cathartica seed was extracted using n-hexane as solvent in soxhlet extractor. The physicochemical and antioxidants properties of the oil were carried out using standard analytical methods. The fatty acid attributes of the extracted seed oil were determined by Gas Liquid Chromatographic (GLC) method. The results of the physicochemical properties gave the followings: Specific gravity (0.87±0.04 g/cm3), refractive index (1.46±0.02 at 30°C), viscosity (53.12±0.08 mpal/sec), acid value (69.17±0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…The concentration detected in this sample is far lower than the toxicity level thus confirming that C. papaya seeds are safe for consumption. The result presented in this work is comparable to the report of Oyeleke et al [11] on the antinutritional composition of C. papaya seeds.…”
Section: Phytochemical and Antinutritional Composition Of The C Papay...supporting
confidence: 91%
See 1 more Smart Citation
“…The concentration detected in this sample is far lower than the toxicity level thus confirming that C. papaya seeds are safe for consumption. The result presented in this work is comparable to the report of Oyeleke et al [11] on the antinutritional composition of C. papaya seeds.…”
Section: Phytochemical and Antinutritional Composition Of The C Papay...supporting
confidence: 91%
“…It has also been found that the method of preparation of medicinal plants is important in determining the quality and quantity of the bioactive compounds obtained from them. Some studies have been carried out on the phytochemical composition of Carica papaya plant extract [8][9][10] but only few studies have worked on the phytochemical composition of Carica papaya seeds [5,11]. Fewer researchers also investigated the effects of drying techniques and solvents used for extraction on the constituents of the phytochemicals and antioxidant activity of the seeds [12].…”
Section: Introductionmentioning
confidence: 99%
“…A possible reason for the high number is the stage of infection; the country had reached the phase of community transmission [13]. Signs of community transmission were first publicized at a press briefing on April 1, and this later became more evident with 203 positive cases whose sources of infection remain indeterminate, according to the NCDC [14].…”
Section: The Spread Of Covid-19 In Nigeria During the Lockdownmentioning
confidence: 99%